A plasma protein corona enhances the biocompatibility of Au@Fe3O4 Janus particles. (November 2015) - Landgraf, Lisa; Christner, Carolin; Storck, Wiebke; Schick, Isabel; Krumbein, Ines; Dähring, Heidi; Haedicke, Katja; Heinz-Herrmann, Karl; Teichgräber, Ulf; Reichenbach, Jürgen R.; Tremel, Wolfgang; Tenzer, Stefan; et al.
Abstract: Au@Fe3 O4 Janus particles (JPs) are heteroparticles with discrete domains defined by different materials. Their tunable composition and morphology confer multimodal and versatile capabilities for use as contrast agents and drug carriers in future medicine. Au@Fe3 O4 JPs have colloidal properties and surface characteristics leading to interactions with proteins in biological fluids. The resulting protein adsorption layer ("protein corona") critically affects their interaction with living matter. Although Au@Fe3 O4 JPs displayed good biocompatibility in a standardized in vitro situation, an in-depth characterization of the protein corona is of prime importance to unravel underlying mechanisms affecting their pathophysiology and biodistribution in vitro and in vivo . Here, we comparatively analyzed the human plasma corona of Au-thiol@Fe3 O4 -SiO2 -PEG JPs (NH2 -functionalized and non-functionalized) and spherical magnetite (Fe3 O4 -SiO2 -PEG) particles and investigated its effects on colloidal stability, biocompatibility and cellular uptake. Label-free quantitative proteomic analyses revealed that complex coronas including almost 180 different proteins were formed within only one minute. Remarkably, in contrast to spherical magnetite particles with surface NH2 groups, the Janus structure prevented aggregation and the adhesion of opsonins. This resulted in an enhanced biocompatibility of corona sheathed JPs compared to spherical magnetite particles and corona-free JPs.